MEMINIMUMKAN BIAYA DISTRIBUSI JERUK MENGGUNAKAN VOGELL’S APPROXIMATION METHOD DENGAN UJI OPTIMAL STEPPING STONE - SHAFARDA, MOH. GHISTA KUSUMA; ASIH, NI MADE; GANDHIADI, G.K. (E-Jurnal Matematika; Vol 8 No 2 (2019)DO - 10.24843/MTK.2019.v08.i02.p244, 2019)
The objective of this reseach is to know the minimum cost distribution of citrus using Vogell's approximation method with stepping stone optimal test. Vogell's approximation method (VAM) is one of the preparation methods of initial feasible solution tables by determining the allocation of distribution on the cell that has the smallest cost and is located on the row or column that has the greatest value of the difference between the two smallest costs. The stepping stone method aims to test the initial solution table by calculating the cost of empty cells passed by the stepping stone path. The research that has been done shows the cost that before the optimization of the distributing costs of kintamani citrus by kintamani citrus farmers using Vogell's approximation method and stepping stone optimal test, it’s obtained that the costs are 85.338.161 rupiahs, while the cost of distributing kintamani citrus by kintamani citrus farmers after the optimization is 75.710.570 rupiahs.